Combining Brain–Computer Interfaces and Assistive Technologies: State-of-the-Art and Challenges - Millán, José del R.; Rupp, Rüdiger; Mueller-Putz, Gernot; Murray-Smith, Roderick; Giugliemma, Claudio; Tangermann, Michael; Vidaurre, Carmen; Cincotti, Febo; Kubler, Andrea; Leeb, Robert; Neuper, Christa; Mueller, Klaus R.; et al. (Frontiers in Neuroscience, 2010)
In recent years, new research has brought the field of EEG-based Brain-Computer Interfacing (BCI) out of its infancy and into a phase of relative maturity through many demonstrated prototypes such as brain-controlled wheelchairs, keyboards, and computer games. With this proof-of-concept phase in the past, the time is now ripe to focus on the development of practical BCI technologies that can be brought out of the lab and into real-world applications. In particular, we focus on the prospect of improving the lives of countless disabled individuals through a combination of BCI technology with existing assistive technologies (AT). In pursuit of more practical BCIs for use outside of the lab, in this paper, we identify four application areas where disabled individuals could greatly benefit from advancements in BCI technology, namely,“Communication & Control”, “Motor Substitution”, “Entertainment”, and “Motor Recovery”. We review the current state of the art and possible future developments, while discussing the main research issues in these four areas. In particular, we expect the most progress in the development of technologies such as hybrid BCI architectures, user-machine adaptation algorithms, the exploitation of users’ mental states for BCI reliability and confidence measures, the incorporation of principles in human-computer interaction (HCI) to improve BCI usability, and the development of novel BCI technology including better EEG devices.